1974
DOI: 10.1021/bi00721a030
|View full text |Cite
|
Sign up to set email alerts
|

Proton transfer mass spectrometry of underivatized peptides

Abstract: Proton transfer spectra of the following underivatized peptides have been studied in a tandem mass spec-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…These higher mass ions decreased in relative abundance with increasing repeller voltage; so we consider that they result in part from gaseous ion-molecule reactions. Table I1 shows the in-beam/CI spectrum of arginine obtained at 260 "C. As mentioned earlier, it is quite similar to the rapid heating spectrum obtained using a heating rate of 5 "C/s (9,10).…”
Section: Resultssupporting
confidence: 70%
“…These higher mass ions decreased in relative abundance with increasing repeller voltage; so we consider that they result in part from gaseous ion-molecule reactions. Table I1 shows the in-beam/CI spectrum of arginine obtained at 260 "C. As mentioned earlier, it is quite similar to the rapid heating spectrum obtained using a heating rate of 5 "C/s (9,10).…”
Section: Resultssupporting
confidence: 70%
“…(2) Friedman has suggested that the nonequilibrium evaporation of intact molecules is enhanced by the lower intermolecular forces present when the sample is in the form of a thin film. 24,25 In our case the volatility appears to be increased by coating the sample on the Vespel@ surface, rather than relying upon vaporization of molecules from crystals located in a sample holder outside the source. It is also possible that the use of an 'inert' material such as Vespel@ aids the desorption process.…”
Section: Evaluation Of the Role Of The Heating Rate In The Ionizationmentioning
confidence: 92%
“…36 The system falls between conventional direct insertion probe and desorption CI in its ability to handle thermally labile and low volatility compounds.37 Sensitivity is difficult to define since it is dependent on the compounds studied and the form of the high performance liquid chromatographic peaks. In general it appears to be comparable with the direct introduction of a portion of the high performance liquid chromatographic eluant approach, in that full spectra are obtained in the on-line mode from upwards of 100 ng of sample injected on the high performance liquid chromatograph and in the selected ion monitoring mode high pg-low ng samples can be handled.…”
Section: Removal Of Solvent From High Performance Liquid Chromatograpmentioning
confidence: 99%